IT auditing : using controls to protect information assets - Kegerreis, Mike; Davis, Chris (Christopher Michael); Schiller, Mike; Wrozek, Brian (McGraw-Hill, 2020)
Fully updated to cover leading-edge tools and technologies, this in-depth resource explains, step by step, how to implement a successful, enterprise-wide IT audit program. --